Communication in Defense of Nonhuman Animals during an Extinction and Climate Crisis - Freeman, Carrie P.; Almiron, Núria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
As modern science and critical scholarship are beginning to recognize nonhuman animals as fellow subjects and conscious, sentient beings with interests and deserving of respect, moral dilemmas abound as humanity acknowledges the threats our activities pose to human and nonhuman animal life, including the sixth mass extinction, anthropogenic climate change, and widespread exploitation. In this 2022 Special Issue of the Journalism and Media journal, communication professors Carrie Freeman and Núria Almiron curated scholarship assessing the impact this environmental havoc is having on nonhuman animals living in nature (including those free-roaming animals who coexist in our urban spaces) and the vital role that media and communication play in contributing to and remedying these crises. Seven scholars across the USA and Spain contributed chapters exploring how issues affecting "wildlife" (such as octopuses, sharks, coyotes, parakeets, and fishes) are constructed in media and political discourses or are perceived and acted upon by public media, and the authors provide prescriptions to problems facing animals in nature, offering constructive guidance to communicators (from activists to journalists to film-makers).